MAML2-Rearranged Primary Central Mucoepidermoid Carcinoma of the Mandible as an Incidental Finding: A Case Report and Review of the Literature of Molecularly Confirmed Cases - Sarah E. Aguirre; Donald Tyler; Adepitan A. Owosho (Case Reports in Dentistry)
This report presents an extremely rare case of MAML2-rearranged primary central mucoepidermoid carcinoma (MEC) of the mandible that was discovered as an incidental finding. Our review of the literature identified 36 cases of MAML2-rearranged intraosseous lesions of the jaw (30 central MECs, 5 odontogenic cysts with mucous prosoplasia, and 1 glandular odontogenic cyst). Given the therapeutic indications for a diagnosis of MEC (a malignant neoplasm), MAML2 rearrangement should be confirmed in suspected cases of central MEC.